How people grow : what the Bible reveals about personal growth - Cloud, Henry; Townsend, John Sims, 1952- (Grand Rapids, Mich. : Zondervan, 2001)
In this book, Dr. Henry Cloud and Dr. John Townsend give you age-old keys to growth from the Scriptures, with life applications that may be different from what you've always thought and were told. Whether life is going well or whether you're struggling in some area, the insights in this book are essential to progressing spiritually, relationally and emotionally.
Harder than I thought -- Seeing the big picture -- How the big picture affects the small -- The God of grace -- Jesus : our example for living -- The Holy Spirit -- Gods plan A : people -- Open spaces : the power of acceptance -- Getting to the warmth of forgiveness -- The gardener's handbook : the Bible -- No pain, no gain : the role of suffering and grief -- Growing tasty fruit : becoming a righteous person -- The value of pruning : discipline -- Water from a deeper well : spiritual poverty -- Following the gardener : obedience -- Pulling the weeds : the problem of sin and temptation -- Facing reality : how truth deepens growth -- Putting on the gloves : the importance of activity -- Waiting for the harvest : time.
Includes index.
Keywords: Self-actualization (Psychology) -- Religious aspects -- Christianity; Christian life -- Biblical teaching; Christian life -- Biblical teaching; Self-actualization (Psychology) -- Religious aspects -- Christianity